Development of the Potentiometric Method for Measurement of Cu - Rani Nawang Sari; Poedji Loekitowati Hariani; Suheryanto Suheryanto (IJFAC (Indonesian Journal of Fundamental and Applied Chemistry), 2019)
Potentiometry is one of method on measuring metals based on cell potential. Measurements using potentiometry are divided into comparative cells and concentration cells. Concentration cells are measurements of a cell's potential by using two solutions with different concentrations. The aim of this study was to develop a concentration cell potentiometric method equipped with applications so measurements are easier and faster. The added application able to calculate the results of experiments so that the calculation process becomes faster and easier. Validation results give the results of the R the value of 0.9990; LoD 7.6484x10-7, LoQ 6.2103x10-7, RSD 0.64%, and recovery 98.05%. This optimum measurement was carried out at 30 oC and pH 5. The results of Cu measurements in well water obtained the result of 0.9633 ppm. Measurements using the development of this method, get good validation results and can be used on measurements similar to those in the aquatic environment. Keywords: Potentiometry, cell concentration, Copper (Cu), validation, aquatic environment